Graphene oxide exhibits differential mechanistic action towards Gram-positive and Gram-negative bacteria - Pulingam, Thiruchelvi; Thong, Kwai Lin; Ali, Md. Eaqub; Appaturi, Jimmy Nelson; Dinshaw, Ignatius Julian; Ong, Zhan Yuin; Leo, Bey Fen (Elsevier, 2019)
The antibacterial nature of graphene oxide (GO) has stimulated wide interest in the medical field. Although the antibacterial activity of GO towards bacteria has been well studied, a deeper understanding of the mechanism of action of GO is still lacking. The objective of the study was to elucidate the difference in the interactions of GO towards Gram-positive and Gram-negative bacteria. The synthesized GO was characterized by Ultraviolet–visible spectroscopy (UV–vis), Raman and Attenuated Total Reflectance-Fourier-transform infrared spectroscopy (ATR-FTIR). Viability, time-kill and Lactose Dehydrogenase (LDH) release assays were carried out along with FESEM, TEM and ATR-FTIR analysis of GO treated bacterial cells. Characterizations of synthesized GO confirmed the transition of graphene to GO and the antibacterial activity of GO was concentration and time-dependent. Loss of membrane integrity in bacteria was enhanced with increasing GO concentrations and this corresponded to the elevated release of LDH in the reaction medium. Surface morphology of GO treated bacterial culture showed apparent differences in the mechanism of action of GO towards Gram-positive and Gram-negative bacteria where cell entrapment was mainly observed for Gram-positive Staphylococcus aureus and Enterococcus faecalis whereas membrane disruption due to physical contact was noted for Gram-negative Escherichia coli and Pseudomonas aeruginosa. ATR-FTIR characterizations of the GO treated bacterial cells showed changes in the fatty acids, amide I and amide II of proteins, peptides and amino acid regions compared to untreated bacterial cells. Therefore, the data generated further enhance our understanding of the antibacterial activity of GO towards bacteria. © 2019